Effect of phosphorus placement in reduced tillage crop production - Martin, Kent Lee (Kansas State University, 2009)
A number of questions are being raised concerning phosphorus (P) management as producers switch to minimum or no-tillage cropping systems. Benefits of P application are site specific and potential advantages need to be evaluated for each location. Deep band application effects on crop yield and soil P distribution have been studied, but conclusive results are lacking because of the complexity of environment and P placement interactions, particularly in moisture limited environments. Challenges in soil test sampling and interpretation have also affected P management in these reduced and no-tillage systems because of decreased confidence in soil test P data. The objectives of this research were to evaluate crop responses to P application rate and placement and to study the distribution of soil P concentration, both vertically and laterally at a number of locations in Kansas. This research shows that crop growth at the sites evaluated was not negatively affected by P stratification, which was present at all sites at the beginning of the study. Phosphorus placement methods (broadcast and deep band) did not have significant effects on P responses. However, P application was required to achieve maximum yields at sites with low soil P, but high P sites did not consistently respond to P application. When P fertilizer was broadcast, shallow soil depths continued to have high soil test P, while deep band application increased soil P in the 7.6 to 15 cm depth. The addition of starter application with deep banding of P generally resulted in a more even vertical distribution of soil P. Soil test P data also demonstrated that the presence of bands can be confirmed through soil sampling, but the confidence of soil test P data in a vertical and lateral stratified soil was decreased. Soil samples taken from the band area had highly variable P (high coefficient of variation) concentrations likely due to an inability to sample from within the P band or variability in P application. Soil sampling in these management systems proves to be challenging and will need further research to identify improved methods for soil test P sampling and interpretation.
Keywords: phosphorus; stratification; Agriculture, Agronomy (0285)